Recommendations on successful quarantine of pure exotic sheep breed at Bangladesh Livestock Research Institute in Bangladesh - Giasuddin, Md.; Rahman, Md. Mamunur; Hassan, Md. Zakir; Yesmin, Morsheda; Ahmed, Sadek; Ershaduzzaman, Md. (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The objective of this study was to examine the newly arrived pure breed sheep considering antibody against some diseases and immunization of the animal against endemic diseases of hosting area according to species. Materials and methods: A total of 42 pure exotic breed of sheep, originated from Australia namely Parendale (n=14), Suffolk (n=13) and Dorper (n=15), imported by the Bangladesh Livestock Research Institute (BLRI) were used in this study. Before shifting the animals to sheep farm, 1-month quarantine was done in an isolated shed by following step by step technique; first week was used for close observation, second week for immunization of animal against endemic diseases, third week for monitoring and observation against immunization, and the fourth week was used for determination of animal health status and immunity level. On day 1 and 2, the sheep remained at full rest along with supplied habituated feed, saline and drinking water. On day 3, fecal sample was collected from all animals to measure parasitic load. On day 4, blood and oculo-nasal discharge samples were collected to detect blood protozoa, peste des petits ruminants (PPR), foot and mouth disease (FMD) and other infectious zoonotic diseases like anthrax, brucellosis and tuberculosis. In the second week, immunization was done against PPR, FMD and hemorrhagic septisemia (HS) at two days interval. Farm biosecurity and biosafety for the workers and officers was maintained according to standard guideline. In the third week, the animals continued to be under close observation. On day 29, the antibody level produced due to vaccination was measured. Results: Parasitic load was found to be very low, and blood protozoa, PPR, FMD, anthrax, brucellosis and tuberculosis were negative. The antibody titer was detected at the acceptable level in sheep on day 29. The quarantine committee decided that the sheep were ready to transfer to the farm along with some recommendations. After completion of 1-month quarantine period, all sheep could not transmit any diseases in Bangladesh. Conclusion: Quarantine is mandatory for entering any new animal in a new area that gives the outline of different new diseases. It also acts as radar of exotic disease in a country. So, this quarantine technique serves the purpose for livestock owners effectively. http://doi.org/10.5455/javar.2018.e249